Cyclops: A Nanomaterial-based, Battery-Free Intraocular Pressure (IOP) Monitoring System inside Contact Lens - Li, Liyao; Shang, Bozhao; Wu, Yun; Xiong, Jie; Chen, Xiaojiang; Xie, Yaxiong (NSDI'24, 2024)
Intraocular pressure (IOP), commonly known as eye pressure, is a critical physiological parameter related to health. Contact lens-based IOP sensing has garnered significant attention in research. Existing research has been focusing on developing the sensor itself, so the techniques used to read sensing data only support a reading range of several centimeters, becoming the main obstacle for real-world deployment. This paper presents Cyclops, the first battery-free IOP sensing system integrated into a contact lens, which overcomes the proximity constraints of traditional reading methods. Cyclops features a three-layer antenna comprising two metallic layers and a nanomaterial-based sensing layer in between. This innovative antenna serves a dual purpose, functioning as both a pressure sensor and a communication antenna simultaneously. The antenna is connected to an RFID chip, which utilizes a low-power self-tuning circuit to achieve high-precision pressure sensing, akin to a 9-bit ADC. Extensive experimental results demonstrate that Cyclops supports communication at meter-level distances, and its IOP measurement accuracy surpasses that of commercial portable IOP measurement devices.